2018
DOI: 10.1016/j.jimonfin.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning carry trades: Less risk, more return

Abstract: Prior studies show that extreme interest rate differentials (IRDs) and high foreign exchange rate (FX) volatility have substantial explanatory power for the validity of UIP. We show that these contemporaneous drivers also have predictive power by implementing a conditional currency carry trade (CT) strategy that excludes regimes for which UIP is likely to hold. Conditioning high FX volatility only, or on both FX volatility and extreme IRDs outperforms the base-case unconditional CT strategy in virtually any of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The carry trade strategy also represents the magnitude of the forward premium, and the reduction in the profits of carry traders with increasing investment size causes the forward premium anomaly to disappear [10]. Carry trade returns, which have been proven to have long-range dependence in developed markets, can be explained mostly by the risk factors related to the foreign exchange market and have predictive power with other contemporaneous drivers, such as interest rate differentials and foreign exchange rate volatility [53][54][55][56]. By comparing a portfolio based on expectations with trend and carry trade portfolios, it is found that carry trade strategies become less profitable with low interest rate differentials and note that the time-varying characteristic of monetary policy affects expectations [57].…”
Section: Heterogeneous Agentsmentioning
confidence: 99%
“…The carry trade strategy also represents the magnitude of the forward premium, and the reduction in the profits of carry traders with increasing investment size causes the forward premium anomaly to disappear [10]. Carry trade returns, which have been proven to have long-range dependence in developed markets, can be explained mostly by the risk factors related to the foreign exchange market and have predictive power with other contemporaneous drivers, such as interest rate differentials and foreign exchange rate volatility [53][54][55][56]. By comparing a portfolio based on expectations with trend and carry trade portfolios, it is found that carry trade strategies become less profitable with low interest rate differentials and note that the time-varying characteristic of monetary policy affects expectations [57].…”
Section: Heterogeneous Agentsmentioning
confidence: 99%